Analysis of flow and heat transfer during the impingement of a diesel spray on a wall using large eddy simulation. (September 2019) - Kawanabe, Hiroshi; Komae, Jun; Ishiyama, Takuji
Numerical calculations were carried out to investigate the formation of a fuel–air mixture as well as ignition and combustion processes associated with a diesel spray impinging on a wall. This was performed by modeling the spray formed by injecting n -heptane into a constant-volume vessel under high temperature and pressure, with the fuel droplets described by a discrete droplet model. The flow and turbulent diffusion processes were calculated based on the large eddy simulation method to simulate the formation of a local non-homogeneous mixture and the accompanying heat release. The flame structure and heat transfer to the wall during impingement were also assessed. The results show that heat transfer to the wall is increased in the peripheral region around the stagnation point, as a result of the high temperature and thin boundary layer. Conversely, in the outer region, the heat transfer decreases as the boundary layer becomes more developed.